Extraction of Jute Genomic DNA: Difficulties and Solutions - Hossain, A. K. M. Shahadat; Latif, Md. Abdul; Biswas, Bipul Kumar; Saclain, Saidin; Salahuddin, Md; Sayed, M. Abu; Hussain, Md. Mahboob; Moniruzzaman, Sheik Md; Islam, Md. Shahidul (International Journal of Applied Sciences and Biotechnology, 2014)
The plant parts of jute are composed of highly viscous substances and phenolic compounds which make nuisance to extract good quality genomic DNA (gDNA). Here different methods viz., phenol chloroform isoamylalcohol extraction and ethanol precipitation method; potassium acetate method and Cetyl trimethylammonium bromide (CTAB) method were applied for isolating the jute gDNA from leaves of 14 and 40 day’s plants. All of these methods were unable to extract good quality gDNA from jute leaves. That is why, in this experiment, the concentration and chemical compositions of CTAB method were modified for obtaining good quality jute gDNA. Polyvinylpyrrolidone (PVP) was added in the CTAB extraction buffer and β mercaptoethanol was used while grinding the leaf tissues with CTAB extraction buffer. It was found that good quality gDNA was obtained using modified CTAB method from 14 day’s plant’s leaves but low quality gDNA was obtained from 40 day’s plant’s leaves. These were confirmed by 0.8% agarose gel electrophoresis. Considering the visual quality of the banding patterns and their reproducibly MHR24 (5/-TTCCCTCCCA-3/) and MHR21 (5-/CCCGAAGCGA-3/) primers were selected out of 8 Random Amplified Polymorphic DNA (RAPD) primers for PCR. A total number of 11 loci were identified by these RAPD primers. Popgen32 software was used for analyzing the RAPD data. The number of polymorphic loci was one and the percentage was 9.09 which stated that a low level of genetic variations was existed among the jute accessions. In the dendrogram, jute accession CC875 (C. capsularis) was grouped in one cluster while CC894 (C. capsularis) and CC896 (C. capsularis) accessions were grouped in another cluster. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11320 Int J Appl Sci Biotechnol, Vol. 2(4): 516-520